The use of peripheral blood cells as an assessment of inflammation in prostate cancer in patients attending in surgery department at ESUT teaching hospital, Parklane, Enugu, Nigeria - Soronnadi, Clara N.; Ibeh, Nancy C.; Ugwene, Francis O.; Amilo, Grace I.; Ede, Anthony J. (International Journal of Research in Medical Sciences, 2020)
Background: Full blood count (FBC) is a prerequisite investigation requested from all prostate cancer (PCa) patients pre and post treatment, poor parameter influences the outcome of cancers. Methods: Total subjects consisted of 84 male subjects between the ages 41 to >80 years. Longitudinal study was conducted. Controls and test samples were collected at diagnosis and at different stages of the treatment. Demographic information was obtained using a questionnaire. The data was analyzed using IBM statistical package for social sciences (SPSS) PC, version 20.0; SPSS Inc., Chicago, III., USA; the receiver operating characteristic curve (ROC) curve was obtained via neutrophil-to-lymphocyte ratio (NLR), lymphocyte-to-monocyte ratio (LMR) and platelet-to-lymphocyte ratio (PLR) ratios cut-off determinations. Cox proportional-hazards regression analyses the prognostic factors (duration, ratios) and overall survival (diagnosis to death or last follow-up). A paired sample t-test compared test of significance in pre/post treatment results. The analysis of variance (ANOVA) and Tukey HSD post-hoc, test susceptibility within age groups was done. Results: Increased NLR and LMR were significantly associated with increased hazard ratio (HR) and OS at p<0.05 while PLR, no significant difference at P>0.05 in PCa. In complete blood count (CBC) and erythrocytic sedimentation rate (ESR), control and treatment period, all red blood cell (RBC) parameters showed a significant decrease at p<0.05 in treatment results compared to the pre-treatment results while total platelet (TPLT), total white blood cells (TWBC), NC, LC, ESR showed significant increase at p<0.05 in treatment results compared to pre-treatment results. Age group 41-50 years showed more susceptibility than other age groups with significant decrease at p<0.05 in NC, LC and increased MC. Conclusions: This study supports CBC and ESR biomarkers as a prognostic tool in early detection, treatment and monitoring of disease progression in these subjects.